Effects of fertilization and concentrate feeding on water quality and growth performance of Nile tilapia (Oreochromis niloticus) grown in concrete tanks - Sebastian W., Chenyambuga; Renalda N., Munubi; Nazael A., Madalla; Kwamena, Quagrainie; Emmanuel, Frimpong; Hillary, Egna (African Science Publications, 2020)
An experiment was conducted to compare the effects of fertilizer application alone, concentrate feeding alone and combination of fertilization and feeding on water quality parameters and growth performance of sex-reversed Nile tilapia (Oreochromis niloticus). Three treatments (weekly fertilization with urea and Diammonium Phosphate (DAP), concentrate feeding at 5% of fish body weight and weekly fertilization with urea and DAP plus concentrate feeding at 2.5% of fish body weight) were randomly allotted to nine concrete tanks. Three fingerlings per m2 were stocked in the tanks and grown for 166 days. Results indicated that treatment had significant effect (p ≤ 0.001) on water Dissolved Oxygen (DO), conductivity, total dissolved solids, nitrate and phosphorus but not on pH, salinity, temperature, ammonia and alkalinity. Fish cultured under the combination of feeding and fertilization had higher (p ≤ 0.0001) weight gain (257.37 ± 5.71 g), growth rate (1.50 ± 0.04 g/day), yield (13,128.35 kg/ha/year) and lower Feed Conversion Ratio (FCR) (1.89 ± 0.03) than those reared under feeding alone and fertilization alone. It is concluded that the combination of weekly fertilization and concentrate feeding at 2.5% of fish body weight is better than either weekly fertilization alone or feeding alone at 5% of fish body weight.
Keywords: Feed conversion efficiency, Growth rate, Yield, Nile tilapia, Water quality parameters